Cost management: the implementation of the Activity-Based Costing method in sterile processing department - Jericó, Marli de Carvalho; Castilho, Valéria (Revista da Escola de Enfermagem da USP, 2010)
This exploratory case study was performed aiming at implementing the Activity-based Costing (ABC) method in a Sterile Processing Department (SPD) of a major teaching hospital. Data collection was performed throughout 2006. Documentary research techniques and non participant closed observation were used. The ABC implementation allowed for learning the activity-based costing of both the chemical and physical disinfection cycle/load: (9.95) and (12.63), respectively; as well as the cost for sterilization by steam under pressure (autoclave) (31.37) and low temperature steam and gaseous formaldehyde sterilization (LTSF) (255.28). The information provided by the ABC method has optimized the overall understanding of the cost driver process and provided the foundation for assessing performance and improvement in the SPD processes.